Prediction of corrosion failure probability of buried oil and gas pipeline based on an RBF neural network - Zhao, Lexin; Luo, Zhengshan; Deng, Guangya; Shi, Victor (Frontiers in Earth Science, 2023)
Risk assessment is critical to ensure the safe operation of oil and gas pipeline systems. The core content of such risk assessment is to quantitatively and accurately determine the failure probability of the pipelines. Hence, this study combines the MATLAB neural network toolbox and adopts the RBF neural network with a strong nonlinear mapping relationship to build a corrosion failure probability prediction model for buried oil and gas gathering and transmission pipelines. Based on the hazard identification of pipeline corrosion failure, the model summarizes the causes of corrosion failure and determines the input and output vectors of the neural network based on the fault tree. According to the selected learning samples, through the design and training of network parameters, the RBF neural network that can predict the system failure probability is finally obtained. Taking the failure probability of 30 groups of high-pressure gathering and transmission pipelines of gas storage as an example, the capability of inputting the probability of the bottom event and outputting the probability of the top event is demonstrated through training data. Our results show that the calculated failure probability based on the fault tree analysis model is consistent with the predicted failure probability based on the RBF neural network model. Hence, the RBF neural network model is shown to be reliable in predicting the corrosion failure probability of buried pipelines.